Impact of Medicare’s Bundled Payments Initiative on Patient Selection, Payments, and Outcomes for PCI and CABG - McNeely, Christian (Circ Cardiovasc Qual Outcomes, 2020)
BACKGROUND: The Center for Medicare and Medicaid Innovation (CMMI) launched the Bundled Payments for Care Initiative (BPCI) in 2013. Its effect on payments and outcomes for percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) is unknown. METHODS AND RESULTS: We used Medicare inpatient files to identify index admissions for PCI and CABG from 2013 through 2016 at BPCI hospitals and matched control hospitals, and difference in differences (DID) models to compare the two groups. Our primary outcome was the change in standardized Medicare allowed payments per 90-day episode. Secondary outcomes included changes in patient selection, discharge to post-acute care (PAC), length of stay (LOS), emergency department use, readmissions, and mortality. 42 hospitals joined BPCI for PCI and 46 for CABG. There were no differential changes in patient selection between BPCI and control hospitals. Baseline Medicare payments per episode for PCI were $20,164 at BPCI hospitals, and $19,955 at control hospitals. For PCI, payments increased at both BPCI and control hospitals during the intervention period, such that there was no significant difference-in-difference (BPCI hospitals + $673, p=0.048; control hospitals + $551, p=0.022; DID $122, p=0.768). For CABG, payments at both BPCI and control hospitals decreased during the intervention period (BPCI baseline, $36,925, change −$2,918, p<0.001; control baseline, $36,877, change −$2,618, p<0.001; DID, $300; p=0.730). For both PCI and CABG, BPCI participation was not associated with changes in mortality, readmissions, or LOS. Among BPCI hospitals, ED use differentially increased for patients undergoing PCI and decreased for patients undergoing CABG. CONCLUSIONS: Participation in episode-based payment for PCI and CABG was not associated with changes in patient selection, payments, LOS, or clinical outcomes.